Literature Review of: Decision Support System: Organization, Human Resources and Knowledge Management - Apriyansyah, Hijrah (Dinasti Publisher, 2022)
Previous research is very important in scientific research or article. The theory and phenomena of the relationship or influence between variables are strengthened by previous research or relevant research. This article examines the variables that influence the Decision Support System, specifically Organization, Human Resources, and Knowledge Management, as well as doing a literature review on Decision Support System Management. The purpose of this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Organization influences the Decision Support System; 2) Human Resources affect the Decision Support System; and 3) Knowledge Management influences the Decision Support System.